Geopolymer-based concrete cementing material and preparation method thereof
A geopolymer-based concrete formulation using industrial and construction waste enhances durability and thermal stability, addressing high cost and temperature sensitivity issues, suitable for construction and highways.
Patent Information
- Application Number
- CN202411347373.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Geopolymer-based concrete faces challenges of high cost, temperature sensitivity, poor durability, and porosity leading to water absorption and surface issues, limiting its application under extreme conditions.
A geopolymer-based concrete formulation using industrial and construction waste, including fly ash, silica fume, carbide slag, biochar, waste plastic, and rubber particles, with specific additives and a preparation method involving mixing and curing, to enhance strength and durability.
The solution provides a cost-effective, durable, and thermally stable concrete with improved mechanical properties and reduced thermal conductivity, suitable for construction and highway applications.
Smart Images

Figure BDA0005061344570000091
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of concrete, and in particular relates to a geopolymer-based concrete cementitious material and a preparation method thereof. Background Art
[0002] Geopolymer-based concrete, a new green building material, has attracted widespread attention in recent years in academia and engineering. Geopolymer-based concrete is primarily made from a wide range of industrial solid waste materials, such as metakaolin, fly ash, steel slag, and blast furnace slag. These waste materials, when activated by chemical activators, can form a three-dimensional, high-performance networked cement. Compared to traditional Portland cement, geopolymer-based concrete requires less energy and emits fewer carbon emissions during its preparation. Research indicates that carbon emissions during the preparation of geopolymer cement are only approximately one-fifth of those of ordinary Portland cement, and overall carbon emissions can be reduced by 26% to 45%. Geopolymer-based concrete exhibits excellent compressive and flexural strength, as well as good resistance to acid and alkali corrosion, freeze-thaw cycles, and carbonation. These properties enable geopolymer-based concrete to perform well in a variety of engineering environments. Due to its unique environmental and mechanical properties, geopolymer-based concrete is considered one of the best alternatives to ordinary Portland cement-based materials. It holds broad application prospects in green buildings, road construction, bridge engineering, and other fields.
[0003] However, in the prior art, geopolymer-based concrete still has the problems of high cost, temperature sensitivity and poor durability. For example, the current preparation of geopolymer-based concrete generally requires the use of a large amount of chemical stimulants (such as sodium silicate solution) or steam curing to accelerate the reaction, which leads to a relatively high preparation cost. In addition, the low activity of raw materials such as metakaolin and fly ash also increases the difficulty and cost of preparation. Geopolymer-based concrete reacts quickly at high temperatures, develops strength quickly, and may even set quickly, which brings difficulties to construction. At low temperatures, the reaction speed slows down, the setting time is extended, and the strength development is slow. This temperature sensitivity limits the application of geopolymer-based concrete under extreme climatic conditions. In addition, the porosity of geopolymer-based concrete is large and the internal salt content is high, resulting in its fast water absorption rate and high saturation. Under dry-wet cycle conditions, efflorescence and peeling are prone to occur, affecting the appearance and durability of the concrete. At the same time, improper curing can also easily lead to cracks and peeling on the concrete surface.
[0004] Therefore, how to provide a geopolymer-based concrete with low cost, good adaptability and good durability is a technical problem that needs to be solved urgently by those skilled in the art. Summary of the Invention
[0005] In order to solve the above technical problems, the present invention proposes a geopolymer-based concrete cementitious material and a preparation method thereof.
[0006] To achieve the above objectives, the present invention provides the following technical solutions:
[0007] A geopolymer-based concrete cementitious material comprises the following raw materials in parts by weight:
[0008] 30-80 parts of fly ash, 10-30 parts of silica fume, 25-55 parts of carbide slag, 1-2 parts of caustic soda, 3-8 parts of construction waste, 1-5 parts of biochar, 1-3 parts of waste plastic, 3-8 parts of rubber particles, 0.5-15 parts of water reducer and 35-45 parts of water.
[0009] Beneficial effects: The present invention uses industrial waste and construction waste as main raw materials to provide a geopolymer-based concrete cementitious material, wherein the caustic soda in the present invention is an alkaline compound, which generates silicate after contacting with silica in waste glass, fully utilizing the silicon element in the waste glass and further promoting the generation of hydration reaction. In addition, the biochar surface in the present invention has a large number of oxygen-containing functional groups, hydroxyl and carboxyl groups, which can be chemically bonded with the surface of fly ash, silica fume and carbide slag, and can modify the performance of concrete together with silica in construction waste, significantly improving the strength of concrete. In addition, the waste plastics in the present invention can fully contact and wrap with other raw materials, thereby improving the density between the raw materials. Adding them together with rubber particles can significantly improve the high temperature resistance of concrete, while improving properties such as ductility and fatigue resistance at low temperatures.
[0010] Preferably, the rubber particles are prepared by crushing waste tires and soaking them in alkali solution.
[0011] Preferably, the alkali solution is a NaOH solution with a concentration of 0.5-1.5 mol / L.
[0012] Beneficial effects: After alkali treatment, the rubber particles can increase the hydrophilicity and roughness of the surface, which is beneficial to improving the mechanical properties of geopolymer concrete. In addition, zinc stearate may exist on the surface of waste rubber particles, which will lead to poor adhesion between the rubber particles and the geopolymer gel material matrix. The alkaline solution can dissolve and remove the zinc stearate on its surface, which is beneficial to improving the compactness between the aggregate and the geopolymer gel material.
[0013] Preferably, the construction waste is waste glass.
[0014] The main component of the waste glass powder is SiO2, and contains a small amount of Na2SiO3 and CaSiO3.
[0015] Preferably, the waste plastic is EVA plastic.
[0016] Preferably, the water reducing agent comprises the following raw materials in parts by weight:
[0017] 3-8 parts of polyethylene glycol monomethyl ether, 5-15 parts of hydroquinone, 1-3 parts of p-toluenesulfonic acid, 4-6 parts of sodium methacrylate sulfonate, 10-15 parts of maleic anhydride, 3-8 parts of ammonium persulfate, 1-3 parts of defoaming agent and 1-5 parts of sodium bicarbonate.
[0018] Preferably, the biochar is obtained by soaking waste straw in a magnesium chloride solution and then pyrolyzing it under a protective atmosphere.
[0019] Preferably, the pyrolysis temperature is 200-300° C. and the time is 3-6 hours.
[0020] Beneficial effects: The present invention uses magnesium to modify biochar, which can effectively increase the specific surface area of biochar. The biochar obtained by the present invention is rich in functional groups, with a large number of acidic functional groups such as hydroxyl and carboxyl groups on the surface. After further magnesium modification, it can significantly improve the thermal stability and mechanical properties of concrete.
[0021] A method for preparing a geopolymer-based concrete cementitious material comprises the following steps:
[0022] The fly ash, silica fume, carbide slag, biochar and construction waste are ground and mixed evenly, and then the rubber particles are added, and then mixed evenly with the waste plastic under heating conditions to obtain a mixed system.
[0023] The water-reducing agent and caustic soda are dissolved in water to obtain a mixture, which is then evenly mixed with the above-mentioned mixed system, molded, and cured to obtain the geopolymer-based concrete cementitious material.
[0024] Preferably, the heating temperature is 90-110°C.
[0025] Beneficial effects: The preparation method of the present invention is simple, and the waste plastics of the present invention can be melted at 90-110°C, fully contacted with and wrapped with other raw materials, thereby improving the density between the raw materials and improving the rutting resistance of the concrete.
[0026] Compared with the prior art, the present invention has the following advantages and technical effects:
[0027] This invention provides a geopolymer-based concrete cementitious material using industrial and construction waste as primary raw materials. The raw materials interact and synergize with each other, significantly improving the compactness of the geopolymer-based concrete cementitious material and effectively enhancing its high-temperature resistance and mechanical properties. It can be widely used in fields such as construction and highways. Furthermore, the preparation method provided by this invention is simple, and the waste collection and treatment costs are low, facilitating its widespread application. DETAILED DESCRIPTION
[0028] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.
[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below in conjunction with specific embodiments.
[0030] A geopolymer-based concrete cementitious material comprises the following raw materials in parts by weight:
[0031] 30-80 parts of fly ash, 10-30 parts of silica fume, 25-55 parts of carbide slag, 1-2 parts of caustic soda, 3-8 parts of construction waste, 1-5 parts of biochar, 1-3 parts of waste plastic, 3-8 parts of rubber particles, 0.5-15 parts of water reducer and 35-45 parts of water.
[0032] In a preferred embodiment, the rubber particles are prepared by crushing waste tires and soaking them in alkali solution.
[0033] In a preferred embodiment, the alkali solution is a NaOH solution with a concentration of 0.5-1.5 mol / L.
[0034] In a preferred embodiment, the construction waste is waste glass.
[0035] The main component of the waste glass powder is SiO2, and contains a small amount of Na2SiO3 and CaSiO3.
[0036] In a preferred embodiment, the waste plastic is EVA plastic.
[0037] In a preferred embodiment, the water reducing agent comprises the following raw materials in parts by weight:
[0038] 3-8 parts of polyethylene glycol monomethyl ether, 5-15 parts of hydroquinone, 1-3 parts of p-toluenesulfonic acid, 4-6 parts of sodium methacrylate sulfonate, 10-15 parts of maleic anhydride, 3-8 parts of ammonium persulfate, 1-3 parts of defoaming agent and 1-5 parts of sodium bicarbonate.
[0039] In a preferred embodiment, the biochar is obtained by soaking waste straw in a magnesium chloride solution and then pyrolyzing it under a protective atmosphere.
[0040] In a preferred embodiment, the pyrolysis temperature is 200-300° C. and the time is 3-6 hours.
[0041] The present invention provides a method for preparing a geopolymer-based concrete cementitious material, comprising the following steps:
[0042] The fly ash, silica fume, carbide slag, biochar, and construction waste are ground and mixed evenly, and then the rubber particles are added, and then mixed evenly with the waste plastic under heating conditions to obtain a mixed system;
[0043] The water-reducing agent and caustic soda are dissolved in water to obtain a mixture, which is then evenly mixed with the above-mentioned mixed system, molded, and cured to obtain the geopolymer-based concrete cementitious material.
[0044] In a preferred embodiment, the heating temperature is 90-110°C.
[0045] Unless otherwise specified, the normal temperature or room temperature described in the embodiments of the present invention refers to 25±3°C.
[0046] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources.
[0047] Among them, waste glass is collected from construction sites, and its main component is SiO2, with a small amount of Na2SiO3 and CaSiO3;
[0048] The scrap tires are nitrile rubber tires;
[0049] Waste EVA plastic is collected from waste wires and cables, with a vinyl acetate content of 15-20%.
[0050] Example 1
[0051] A geopolymer-based concrete cementitious material comprises the following raw materials in parts by weight:
[0052] 50 parts of fly ash, 20 parts of silica fume, 40 parts of carbide slag, 1 part of caustic soda, 5 parts of waste glass, 3 parts of biochar, 2 parts of waste EVA plastic, 5 parts of rubber particles, 10 parts of water reducer and 40 parts of water.
[0053] The water reducing agent includes the following raw materials in parts by weight:
[0054] 5 parts of polyethylene glycol monomethyl ether, 10 parts of hydroquinone, 2 parts of p-toluenesulfonic acid, 5 parts of sodium methacrylate sulfonate, 13 parts of maleic anhydride, 5 parts of ammonium persulfate, 2 parts of defoaming agent and 3 parts of sodium bicarbonate.
[0055] A method for preparing a geopolymer-based concrete cementitious material comprises the following steps:
[0056] (1) After crushing corn stalks to less than 300 mesh, the stalks were immersed in a 3 mol / L magnesium chloride solution at room temperature for 2 h. After drying, the stalks were pyrolyzed at 250 °C for 4 h under a nitrogen atmosphere to obtain biochar.
[0057] (2) The collected waste tires were crushed and immersed in a 1 mol / L NaOH solution for 4 h, and then dried to obtain rubber particles;
[0058] (3) Grinding fly ash, silica fume, carbide slag, biochar, and construction waste to a particle size of 800 or less and then mixing them, then adding rubber particles and heating to 100°C, adding waste EVA plastic while stirring until the waste EVA plastic is completely melted and evenly mixed with the solid powder;
[0059] (4) dissolving the water reducer and caustic soda in water to obtain a mixture, then uniformly mixing the mixture with the mixed system obtained in step (3), filling the mixture into a mold, and curing at room temperature for 28 days to obtain the geopolymer-based concrete cementitious material.
[0060] Example 2
[0061] A geopolymer-based concrete cementitious material comprises the following raw materials in parts by weight:
[0062] 30 parts of fly ash, 10 parts of silica fume, 55 parts of carbide slag, 2 parts of caustic soda, 8 parts of waste glass, 1 part of biochar, 3 parts of waste EVA plastic, 3 parts of rubber particles, 0.5 parts of water reducer and 35 parts of water.
[0063] The water reducing agent includes the following raw materials in parts by weight:
[0064] 3 parts of polyethylene glycol monomethyl ether, 5 parts of hydroquinone, 1 part of p-toluenesulfonic acid, 6 parts of sodium methacrylate sulfonate, 10 parts of maleic anhydride, 8 parts of ammonium persulfate, 3 parts of defoaming agent and 1 part of sodium bicarbonate.
[0065] A method for preparing a geopolymer-based concrete cementitious material comprises the following steps:
[0066] (1) After crushing corn stalks to less than 300 mesh, the stalks were immersed in a 3 mol / L magnesium chloride solution at room temperature for 3 h. After drying, the stalks were pyrolyzed at 200 °C for 6 h under a nitrogen atmosphere to obtain biochar.
[0067] (2) The collected waste tires were crushed and immersed in a 1.5 mol / L NaOH solution for 2 h, and then dried to obtain rubber particles;
[0068] (3) Grinding fly ash, silica fume, carbide slag, biochar, and construction waste to a size of less than 800 mesh and then mixing them, then adding rubber particles and heating to 110°C, adding waste EVA plastic while stirring until the waste EVA plastic is completely melted and evenly mixed with the solid powder;
[0069] (4) dissolving the water reducer and caustic soda in water to obtain a mixture, then uniformly mixing the mixture with the mixed system obtained in step (3), filling the mixture into a mold, and curing at room temperature for 28 days to obtain the geopolymer-based concrete cementitious material.
[0070] Example 3
[0071] A geopolymer-based concrete cementitious material comprises the following raw materials in parts by weight:
[0072] 80 parts of fly ash, 30 parts of silica fume, 25 parts of carbide slag, 1 part of caustic soda, 3 parts of waste glass, 5 parts of biochar, 1 part of waste EVA plastic, 8 parts of rubber particles, 15 parts of water reducer and 45 parts of water.
[0073] The water reducing agent includes the following raw materials in parts by weight:
[0074] 8 parts of polyethylene glycol monomethyl ether, 15 parts of hydroquinone, 3 parts of p-toluenesulfonic acid, 4 parts of sodium methacrylate sulfonate, 15 parts of maleic anhydride, 3 parts of ammonium persulfate, 1 part of defoamer and 5 parts of sodium bicarbonate.
[0075] A method for preparing a geopolymer-based concrete cementitious material comprises the following steps:
[0076] (1) After crushing corn stalks to less than 300 mesh, the stalks were immersed in a 3 mol / L magnesium chloride solution at room temperature for 1 h. After drying, the stalks were pyrolyzed at 300 °C for 3 h under a nitrogen atmosphere to obtain biochar.
[0077] (2) The collected waste tires were crushed and immersed in a 0.5 mol / L NaOH solution for 5 h, and then dried to obtain rubber particles;
[0078] (3) Grinding fly ash, silica fume, carbide slag, biochar, and construction waste to a size of less than 800 mesh and then mixing them, then adding rubber particles and heating to 90°C, adding waste EVA plastic while stirring until the waste EVA plastic is completely melted and evenly mixed with the solid powder;
[0079] (4) dissolving the water reducer and caustic soda in water to obtain a mixture, then uniformly mixing the mixture with the mixed system obtained in step (3), filling the mixture into a mold, and curing at room temperature for 28 days to obtain the geopolymer-based concrete cementitious material.
[0080] Comparative Example 1
[0081] A geopolymer-based concrete cementitious material differs from Example 1 in that caustic soda is not included. Other raw materials, preparation steps, and parameters are the same as those in Example 1.
[0082] Comparative Example 2
[0083] A geopolymer-based concrete cementitious material differs from Example 1 in that waste glass is not included. Other raw materials, preparation steps, and parameters are the same as those in Example 1.
[0084] Comparative Example 3
[0085] A geopolymer-based concrete cementitious material is different from Example 1 in that waste EVA plastic is not included. Other raw materials, preparation steps and parameters are the same as those in Example 1.
[0086] Comparative Example 4
[0087] A geopolymer-based concrete cementitious material differs from Example 1 in that biochar is not included. Other raw materials, preparation steps, and parameters are the same as those in Example 1.
[0088] Comparative Example 5
[0089] A geopolymer-based concrete cementitious material differs from Example 1 in that rubber particles are not included. Other raw materials, preparation steps, and parameters are the same as those in Example 1.
[0090] Technical effect verification example
[0091] 1. Measurement of slurry fluidity
[0092] According to the test method specified in GB / T 2419-2005 Determination of fluidity of cement mortar, the slurries of the geopolymer concrete prepared in Examples 1-3 and Comparative Examples 1-5 were subjected to a jumping table test to measure the fluidity of the slurries. The results are shown in Table 1.
[0093] 2. Compressive strength and thermal conductivity test
[0094] The concrete compressive strength of Examples 1-3 and Comparative Examples 1-5 was tested according to GB / T17671-2021 "Test Method for Strength of Cement Mortar", and the thermal conductivity of the geopolymer recycled fireproof mortar was measured according to GB / T10294-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Insulating Materials"; the results are shown in Table 1.
[0095] Table 1
[0096]
[0097] The results in Table 1 demonstrate that, compared to Comparative Examples 1-5, the geopolymer concretes obtained using Examples 1-3 of the present invention exhibit superior mechanical properties and durability. Furthermore, they possess low thermal conductivity, good thermal insulation, and a certain degree of high-temperature resistance. Furthermore, the reduced thermal conductivity also improves the concrete's ductility at low temperatures. Consequently, the concrete of the present invention exhibits excellent workability, significant economic benefits, and environmental advantages.
[0098] The above are merely preferred embodiments of the present application, but the scope of protection of the present application is not limited thereto. Any changes or substitutions that can be easily conceived by a person skilled in the art within the technical scope disclosed in this application should be included in the scope of protection of the present application. Therefore, the scope of protection of the present application should be based on the scope of protection of the claims.
Claims
1. A geopolymer-based concrete cementitious material, characterized in that: The invention comprises the following raw materials in parts by weight: 30-80 parts of fly ash, 10-30 parts of silica fume, 25-55 parts of carbide slag, 1-2 parts of caustic soda, 3-8 parts of construction waste, 1-5 parts of biochar, 1-3 parts of waste plastics, 3-8 parts of rubber particles, 0.5-15 parts of water reducing agent and 35-45 parts of water.
2. A geopolymer-based concrete cementitious material according to claim 1, characterized in that: The rubber particles are prepared by crushing waste tires and soaking them in alkali solution.
3. A geopolymer-based concrete cementitious material according to claim 2, characterized in that: The alkali solution is a NaOH solution with a concentration of 0.5-1.5 mol / L.
4. The geopolymer-based concrete cementitious material according to claim 1, characterized in that: The construction waste is waste glass.
5. The geopolymer-based concrete cementitious material according to claim 1, characterized in that: The waste plastic is EVA plastic.
6. The geopolymer-based concrete cementitious material according to claim 1, characterized in that: The water reducing agent comprises the following raw materials in parts by weight: 3-8 parts of polyethylene glycol monomethyl ether, 5-15 parts of hydroquinone, 1-3 parts of p-toluenesulfonic acid, 4-6 parts of sodium methacrylate sulfonate, 10-15 parts of maleic anhydride, 3-8 parts of ammonium persulfate, 1-3 parts of defoaming agent and 1-5 parts of sodium bicarbonate.
7. The geopolymer-based concrete cementitious material according to claim 1, characterized in that: The biochar is obtained by soaking waste straw in a magnesium chloride solution and then pyrolyzing it under a protective atmosphere.
8. The geopolymer-based concrete cementitious material according to claim 7, characterized in that: The pyrolysis temperature is 200-300° C. and the time is 3-6 hours.
9. A method for preparing a geopolymer-based concrete cementitious material according to any one of claims 1 to 8, characterized in that: The following steps are involved: The fly ash, silica fume, carbide slag, biochar and construction waste are ground and mixed evenly, and then the rubber particles are added, and then mixed evenly with the waste plastic under heating conditions to obtain a mixed system; The water reducing agent and caustic soda are dissolved in water to obtain a mixture, which is then mixed evenly with the above-mentioned mixed system and then molded and cured to obtain the geopolymer-based concrete cementitious material.
10. The method for preparing a geopolymer-based concrete cementitious material according to claim 9, characterized in that: The heating temperature is 90-110°C.
Citation Information
Patent Citations
Green asphalt concrete-modified asphalt with high durability and preparation method thereof
CN107304112A
Method for preparing gravity energy storage block by using waste incineration bottom ash and waste plastic
CN114772991A
All-solid waste pavement base cementing material and preparation method thereof
CN115557716A
Geopolymer-based concrete material and preparation method thereof
CN116425464A
Gas supply layer deposition method and layer deposition apparatus
KR1020210026898A
